2020
DOI: 10.3151/jact.18.545
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Morphology and Mechanical Behavior of Corroded Prestressing Strands

Abstract: The corrosion morphology and the mechanical behavior of corroded prestressing strands are investigated in the present study. Nineteen corroded strands are obtained through controlling stress level, corrosion time and chloride ion concentration under artificial climate conditions. A total of 119 corrosion pits are counted to investigate the geometric morphology of corrosion pits. A depth-width ratio parameter is first defined to describe the distribution law of corrosion pits, which obeys the lognormal distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…In this context, as pointed out by Yoo et al, 25 nondestructive methods such as radiography, x-ray, endoscopic inspection, or methods by using magnetic field can be adopted to accurately determine defects in strands along the overall length of a PC element and evaluate the position of the most corroded section. Moreover, Wang et al 20 identified other possible nondestructive techniques for the evaluation of the corrosion loss of strand such as the acoustic emission method, the half-cell potential, or the linear polarization resistance or visual inspections reporting corrosion stains or corrosion cracks. In this framework, once the position of the minimum cross-sectional loss is known, a local removal of the thickness of the concrete cover allows the measurement of P max by using the pit depth gauge or other technical instruments.…”
Section: Main Simplifications Of the Scps-modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, as pointed out by Yoo et al, 25 nondestructive methods such as radiography, x-ray, endoscopic inspection, or methods by using magnetic field can be adopted to accurately determine defects in strands along the overall length of a PC element and evaluate the position of the most corroded section. Moreover, Wang et al 20 identified other possible nondestructive techniques for the evaluation of the corrosion loss of strand such as the acoustic emission method, the half-cell potential, or the linear polarization resistance or visual inspections reporting corrosion stains or corrosion cracks. In this framework, once the position of the minimum cross-sectional loss is known, a local removal of the thickness of the concrete cover allows the measurement of P max by using the pit depth gauge or other technical instruments.…”
Section: Main Simplifications Of the Scps-modelmentioning
confidence: 99%
“…In this context, several works have been carried out to investigate the stress-strain relationship of corroded steel rebars, [5][6][7][8][9][10][11][12][13][14][15][16] whereas limited studies have been performed for the prediction of the residual mechanical response of corroded prestressing strands. [17][18][19][20][21][22] In Table 1, the main features of each model are summarized. In detail, the several decay laws proposed by different authors are generally based on one of these parameters: (i) the mass loss, η, of the corroded sample, generally evaluated by adopting the procedure described in the ASTM G1-03 Standard, 23 or (ii) the crosssectional loss, μ, of the corroded prestressing strand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the effect of corrosion on the elastic modulus and yield strength was not obvious in the previous study. For instance, Wang et al (2020) also used the artificial climate corrosion method to corrode the PC steel strands, analyzed the shape of corrosion and its mechanical properties, and found that high stress levels can promote the expansion of corroded microcracks on the surface of steel strands. Finally, the corrosion was divided into slight and severe conditions, and a constitutive model was proposed to predict the stress-strain curve of these corroded PC strands.…”
Section: Introductionmentioning
confidence: 99%
“…In prestressed concrete structures, corrosion of prestressing strands at early stages results in microcracking, deterioration of the bond between strands and concrete, and therefore, in the loss of prestressing force. In an advanced stage, corrosion may result in the rupture of strands [11,12].…”
Section: Introductionmentioning
confidence: 99%